Thallium-doped copper-based halide powder, scintillator film, preparation method and application thereof
Through the preparation of thallium-doped copper-based halide powder and scintillator film, the self-absorption and instability of lead-based halides in X-ray detectors are solved, and the redshift of the luminescence wavelength and the fluorescence performance are improved. The response wavelength of the commercial detector was matched and the commercial scintillator layer was replaced.
Patent Information
- Application Number
- CN202410955249.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-17
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-07-17
AI Technical Summary
The existing lead-based halides have problems with self-absorption, instability and mismatch in X-ray detectors, which limits their application in the field of indirect detection.
The copper-based halide powder and scintillator film were prepared by grinding method, and mixed with polymer composite material and dispersant. The scintillator film was prepared by drop coating and hot pressing method to ensure luminescence. The wavelength is red-shifted to 510nm, with high fluorescence quantum efficiency and short fluorescence decay life, matching the response wavelength of commercial X-ray flat plate detectors.
The light yield and resolution are improved, the aggregation phenomenon of copper-based halide powder is overcome, and the stable fluorescence performance is achieved. The luminescence wavelength is matched with the commercial detector, and the commercial scintillator layer is replaced.
Smart Images

Figure CN118496848B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of indirect detection in radiation detection, and in particular to thallium-doped copper-based halide powder, thallium-doped scintillator film, preparation method and application thereof. Background Art
[0002] X-ray detectors are widely used in medical diagnosis, radiotherapy, safety inspection, geological exploration, deep space exploration, industrial non-destructive testing, environmental radiation monitoring and other fields. As a scintillator layer that converts X-ray photons into visible light photons, metal halide perovskites have attracted widespread attention due to their excellent performance. Among them, lead-based halides have properties such as high absorption coefficient, high fluorescence quantum efficiency, and adjustable emission wavelength. However, the self-absorption problem caused by the small Stokes shift limits its light yield and resolution. In addition, water, oxygen, high temperature and other environments will also accelerate the aging and decomposition of lead-based halides. The resulting instability is also one of the factors limiting the popularization of this material in the field of indirect detection. Summary of the invention
[0003] In order to achieve the above-mentioned object, the first aspect of the present invention provides a thallium-doped copper-based halide powder, the chemical composition formula of the thallium-doped copper-based halide powder includes: A3Cu2X5:TlX; wherein A represents an alkali metal element and X represents a halogen element.
[0004] According to an embodiment of the present invention, the alkali metal element includes at least one of the following: Cs + 、Na + , K + , Rb + ; Halogen elements include at least one of the following: I - Br - , Cl - .
[0005] The second aspect of the present invention provides a thallium-doped scintillator film, which is prepared using thallium-doped copper-based halide powder. The chemical composition formula of the thallium-doped copper-based halide powder includes: A3Cu2X5:TlX; wherein A represents an alkali metal element and X represents a halogen element.
[0006] The third aspect of the present invention provides a method for preparing a thallium-doped copper-based halide powder, comprising: grinding solid materials of AX, CuX and TlX by a grinding method to obtain a thallium-doped copper-based halide powder; wherein A represents an alkali metal element, and X represents a halogen element; the molar ratio of AX to CuX is 3:2; and the molar ratio of TlX to AX is 0.4% to 2.4%.
[0007] According to an embodiment of the present invention, the grinding time is 3 to 12 hours; the grinding speed is 500 to 2000 r / min; and the grinding method includes dry grinding and / or wet grinding.
[0008] The fourth aspect of the present invention provides a method for preparing a thallium-doped scintillator film, comprising: mixing thallium-doped copper-based halide powder, a polymer composite material and a dispersant to obtain a powder dispersion, wherein the chemical composition formula of the thallium-doped copper-based halide powder comprises: A3Cu2X5:TlX, A represents an alkali metal element, and X represents a halogen element; and film-forming the powder dispersion to obtain a thallium-doped scintillator film.
[0009] According to an embodiment of the present invention, the film forming method includes one of the following: drip coating, blade coating, and spray coating; the mass ratio of thallium-doped copper-based halide powder to the polymer composite material is 1:1~500:1; the polymer composite material includes one of the following: polymethyl methacrylate, polydimethylsiloxane, polyvinyl alcohol, polyvinyl butyral, polystyrene; the dispersant includes at least one of the following: dimethylformamide, dimethyl sulfoxide, γ-hydroxybutyrolactone, β-mercaptoethanol, nitrogen methyl pyrrolidone, dimethylacetamide, anhydrous ethanol and toluene.
[0010] According to an embodiment of the present invention, a film forming method includes: a drop coating method; forming a film on a powder dispersion to obtain a thallium-doped scintillator film, including: drop coating the powder dispersion on a substrate so that an initial thallium-doped scintillator film is obtained after the dispersant is volatilized; and hot pressing the initial thallium-doped scintillator film to obtain a thallium-doped scintillator film.
[0011] According to an embodiment of the present invention, the pressure of hot pressing is 5-20t; the temperature of hot pressing is 100-300 o C; The hot pressing time is 1~10min.
[0012] A fifth aspect of the present invention provides an application of a thallium-doped copper-based halide powder or a thallium-doped scintillator film in the field of radiation detectors; wherein the thallium-doped copper-based halide powder is the above-mentioned thallium-doped copper-based halide powder or the thallium-doped copper-based halide powder prepared by the above-mentioned preparation method; the thallium-doped scintillator film is the above-mentioned thallium-doped scintillator film or the thallium-doped scintillator film prepared by the above-mentioned preparation method.
[0013] According to an embodiment of the present invention, the thallium-doped copper-based halide powder provided by the present invention has a +As a substitution doping of alkali metal in copper-based halide, the conduction band minimum value of the copper-based halide energy level structure is reduced, thereby reducing its band gap and red-shifting the emission wavelength. Therefore, compared with undoped thallium-doped copper-based halide powder, the emission wavelength of thallium-doped copper-based halide powder is red-shifted to around 510nm, and the fluorescence quantum efficiency is high (about 92%), and the fluorescence decay lifetime is short (about 437ns). Since the emission wavelength of thallium-doped copper-based halide powder is relatively matched with the emission wavelength (around 550nm) of the scintillator (such as CsI:Tl, GOS:Tb) of commercial X-ray flat panel detectors, the thallium-doped copper-based halide powder provided by the present invention can be used to prepare a scintillator film to replace the scintillator layer in the commercial X-ray flat panel detector, while ensuring good fluorescence performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The photoluminescence spectra of the scintillator film obtained in Comparative Example 1 of the present invention and the thallium-doped scintillator film obtained in Example 1 under irradiation with 310 nm ultraviolet light are shown;
[0015] Figure 2 The figure shows the surface morphology of the thallium-doped scintillator film obtained in Example 1 of the present invention observed by a scanning electron microscope;
[0016] Figure 3 The cross-sectional morphology of the thallium-doped scintillator film obtained in Example 1 of the present invention observed by a scanning electron microscope is shown;
[0017] Figure 4 The cross-sectional layered diagram of the thallium-doped scintillator film obtained in Example 1 of the present invention observed by an energy dispersive X-ray spectrometer is shown;
[0018] Figure 5 Shown with Figure 4 Corresponding distribution diagram of each element in the cross section of the thallium-doped scintillator thin film obtained in Example 1 of the present invention;
[0019] Figure 6 The radiant luminescence spectra of the CsI:Tl crystal and the thallium-doped scintillator film obtained in Example 1 of the present invention under X-ray irradiation are shown;
[0020] Figure 7 The time-resolved photoluminescence spectrum of the thallium-doped scintillator film obtained in Example 1 of the present invention under irradiation of a 369nm laser pulse is shown. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.
[0022] In the process of realizing the present invention, it is found that a new type of copper-based halide is considered to be one of the candidate materials in the field of indirect detection due to its excellent photoelectric properties and good stability. The unique self-trapped exciton luminescence mechanism of copper-based halide materials enables them to have a large Stokes shift and almost negligible self-absorption. Thanks to this, the light yield and resolution of copper-based halide scintillator films have been significantly improved. However, the copper-based halide powder prepared by the anti-solvent method currently used is seriously agglomerated and has low fluorescence efficiency. In addition, the scintillators (such as CsI:Tl, GOS:Tb) currently widely used in commercial X-ray flat panel detection have a luminescence wavelength of about 550nm, while the luminescence wavelength of Cs3Cu2I5, a common component in copper-based halides, is located near 450nm, which does not match the response wavelength of the photodetector in commercial X-ray detectors. Therefore, it is very necessary to synthesize a copper-based halide scintillator material with a red-shifted luminescence wavelength while ensuring that its fluorescence properties are not affected.
[0023] Based on this, the first aspect of the present invention provides a thallium-doped copper-based halide powder, the chemical composition formula of the thallium-doped copper-based halide powder includes: A3Cu2X5:TlX; wherein A represents an alkali metal element, and X represents a halogen element.
[0024] According to an embodiment of the present invention, the alkali metal element may include at least one of the following: Cs + 、Na + , K + , Rb + The halogen element may include at least one of the following: - Br - , Cl - .
[0025] For example, the chemical composition of the thallium-doped copper-based halide powder may include, but is not limited to, at least one of the following: Cs3Cu2I5:TlI, Cs3Cu2Br5:TlBr, Cs3Cu2Cl5:TlCl, Na3Cu2I5:TlI, Na3Cu2Br5:TlBr, Na3Cu2Cl5:TlCl, K3Cu2I5:TlI, K3Cu2Br5:TlBr, K3Cu2Cl5:TlCl, Rb3Cu2I5:TlI, Rb3Cu2Br5:TlBr, Rb3Cu2Cl5:TlCl, etc.
[0026] According to an embodiment of the present invention, in the thallium-doped copper-based halide powder, the element composition ratio of A:Cu:Tl, expressed as a molar ratio, may be 750:500:3 to 750:500:18.
[0027] According to an embodiment of the present invention, the thallium-doped copper-based halide powder can be used in a radiation detector.
[0028] According to an embodiment of the present invention, the thallium-doped copper-based halide powder provided by the present invention has a + As a substitution doping of alkali metal in copper-based halide, the conduction band minimum value of the copper-based halide energy level structure is reduced, thereby reducing its band gap and red-shifting the emission wavelength. Therefore, compared with undoped thallium-doped copper-based halide powder, the emission wavelength of thallium-doped copper-based halide powder is red-shifted to around 510nm, and the fluorescence quantum efficiency is high (about 92%), and the fluorescence decay lifetime is short (about 437ns). Since the emission wavelength of thallium-doped copper-based halide powder is relatively matched with the emission wavelength (around 550nm) of the scintillator (such as CsI:Tl, GOS:Tb) of commercial X-ray flat panel detectors, the thallium-doped copper-based halide powder provided by the present invention can be used to prepare a scintillator film to replace the scintillator layer in the commercial X-ray flat panel detector, while ensuring good fluorescence performance.
[0029] The present invention also provides a method for preparing thallium-doped copper-based halide powder, comprising: grinding solid materials of AX, CuX and TlX by a grinding method to obtain thallium-doped copper-based halide powder; wherein A represents an alkali metal element, and X represents a halogen element; the molar ratio of AX to CuX is 3:2; and the molar ratio of TlX to AX is 0.4% to 2.4%.
[0030] According to an embodiment of the present invention, the molar ratio of AX to CuX is 3:2, which can prevent the disproportionation of cuprous ions and the generation of halogen elements, and can also prevent the excessive residue of AX powder, which makes it difficult to clean. The molar ratio of TlX to AX is less than 0.4%, which will cause the luminous wavelength of the thallium-doped copper-based halide to fail to red-shift to 510 nm. The molar ratio of TlX to AX is greater than 2.4%, which will significantly reduce the luminous efficiency of the thallium-doped copper-based halide.
[0031] According to an embodiment of the present invention, the grinding time may be 3 to 12 hours. For example, the grinding time may include but is not limited to 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, and 12 hours.
[0032] According to the embodiment of the present invention, too short a grinding time may result in insufficient grinding, affecting the yield, particle size and purity of the thallium-doped copper-based halide powder. Too long a grinding time may waste time costs.
[0033] According to an embodiment of the present invention, the grinding speed may be 500-2000 r / min. For example, the grinding speed may include but is not limited to 500 r / min, 750 r / min, 1000 r / min, 1250 r / min, 1500 r / min, 1750 r / min, and 2000 r / min.
[0034] According to the embodiment of the present invention, too low a grinding speed may affect the grinding efficiency and the particle size of the thallium-doped copper-based halide powder. Too high a grinding speed may cause damage to the grinder and damage caused by component splitting due to centrifugal force and vibration.
[0035] According to an embodiment of the present invention, the grinding method may include a dry grinding method and / or a wet grinding method.
[0036] For example, the dry grinding method may include directly adding solid materials of AX, CuX and TlX into a grinding jar, placing the jar in a physical grinder for grinding, and obtaining thallium-doped copper-based halide powder.
[0037] The wet grinding method may include adding solid materials of AX, CuX and TlX together with a solvent insoluble in the solid materials into a grinding jar, placing the mixture in a physical grinder for grinding to obtain thallium-doped copper-based halide powder.
[0038] The solvent insoluble in the solid material may include, but is not limited to, at least one of the following: dimethylformamide (DMF), dimethyl sulfoxide (DMSO), γ-hydroxybutyrolactone (GBL), β-mercaptoethanol (2-ME), nitrogenmethylpyrrolidone (NMP), dimethylacetamide (DMAC), anhydrous ethanol and toluene.
[0039] According to an embodiment of the present invention, the grinding jar may include a ball mill jar, but is not limited thereto. The ball mill jar may contain balls made of non-metallic materials, such as agate balls.
[0040] According to another embodiment of the present invention, after grinding, anhydrous ethanol or other solvents may be added to the ball mill to assist in dispersion, and the ultrasonic power may be 100-500 W. After ultrasonic dispersion, the dispersion is centrifuged, and the centrifugal rate may be 3000-7000 r / min. The precipitate is taken and dried, and the drying temperature may be 80 o C~150 o C, drying time can be longer than 5h.
[0041] According to the embodiment of the present invention, the present invention uses a grinding method to prepare thallium-doped copper-based halide powder, which can overcome the problem of serious agglomeration of copper-based halide powder prepared by an anti-solvent method. In addition, thallium-doped copper-based halide powder with high fluorescence quantum yield and short decay time is synthesized at room temperature. It can be applied to radiation detectors.
[0042] The present invention also provides a thallium-doped scintillator film, which is prepared by using thallium-doped copper-based halide powder. The chemical composition formula of the thallium-doped copper-based halide powder includes: A3Cu2X5:TlX; wherein A represents an alkali metal element and X represents a halogen element.
[0043] According to an embodiment of the present invention, the thallium-doped scintillator film has better fluorescence performance under X-ray irradiation than the undoped thallium scintillator film, and the emission wavelength is red-shifted from 450 nm to 510 nm, which is more compatible with the response wavelength of the photodetector in the commonly used X-ray detector.
[0044] In the process of implementing the present invention, it is also found that the scintillators (such as CsI:Tl, GOS:Tb) used in commercial X-ray flat panel detectors are prepared by thermal evaporation or sintering, which requires 1700 o The high temperature of around 30°C has disadvantages such as high energy consumption and long preparation cycle. Therefore, it is necessary to explore a new method that can meet the needs of scintillator preparation.
[0045] Based on this, the present invention also provides a method for preparing a thallium-doped scintillator film, comprising: mixing thallium-doped copper-based halide powder, a polymer composite material and a dispersant to obtain a powder dispersion, wherein the chemical composition formula of the thallium-doped copper-based halide powder comprises: A3Cu2X5:TlX, A represents an alkali metal element, and X represents a halogen element; and film-forming the powder dispersion to obtain a thallium-doped scintillator film.
[0046] According to an embodiment of the present invention, the mass ratio of the thallium-doped copper-based halide powder to the polymer composite material is 1:1 to 500:1. The polymer composite material includes one of the following: polymethyl methacrylate, polydimethylsiloxane, polyvinyl alcohol, polyvinyl butyral, polystyrene; and the dispersant includes at least one of the following: dimethylformamide, dimethyl sulfoxide, γ-hydroxybutyrolactone, β-mercaptoethanol, nitrogen methyl pyrrolidone, dimethylacetamide, anhydrous ethanol, and toluene.
[0047] According to an embodiment of the present invention, the mass ratio ranges of different polymer composites to thallium-doped copper-based halide powders may be different. For example, the mass ratio of thallium-doped copper-based halide powders to PMMA may be in the range of 1:1 to 2:1, the mass ratio of thallium-doped copper-based halide powders to PDMS may be in the range of 1:1 to 10:1, the mass ratio of thallium-doped copper-based halide powders to PVB may be in the range of 25:1 to 500:1, etc.
[0048] According to an embodiment of the present invention, a mass ratio of thallium-doped copper-based halide powder to polymer composite material that is too small will affect the radioluminescence performance and X-ray absorptivity of the scintillator film, while a mass ratio that is too large will lead to uneven dispersion of the dispersion liquid, making it difficult to prepare a uniform scintillator film.
[0049] According to an embodiment of the present invention, the dispersant may include at least one of the following: dimethylformamide, dimethyl sulfoxide, γ-hydroxybutyrolactone, β-mercaptoethanol, nitrogen methyl pyrrolidone, dimethylacetamide, anhydrous ethanol and toluene.
[0050] According to an embodiment of the present invention, the thallium-doped copper-based halide powder, the polymer composite material and the dispersant can be fully stirred by a magnetic particle to obtain a powder dispersion. The stirring temperature can be 60 o C~80 o C, stirring time can be longer than 3h.
[0051] According to an embodiment of the present invention, the film forming method may include one of the following: drip coating, blade coating, and spray coating.
[0052] Preferably, the film-making method may include: drop coating. Film-making the powder dispersion to obtain the thallium-doped scintillator film may include: drop coating the powder dispersion on the substrate to obtain the initial thallium-doped scintillator film after the dispersant is volatilized; and hot pressing the initial thallium-doped scintillator film to obtain the thallium-doped scintillator film.
[0053] According to an embodiment of the present invention, hot pressing can be performed in a hot press. The pressure of hot pressing can be 5-20t; the temperature of hot pressing can be 100-300 o C; The hot pressing time can be 1~10min.
[0054] According to an embodiment of the present invention, through the drop coating method provided by the present invention, a thallium-doped scintillator film with high fluorescence quantum yield and short decay time can be synthesized at room temperature. This film can exhibit good fluorescence performance under X-ray irradiation, and the emission wavelength is around 510nm, which is more matched with the response wavelength of the photodetector in the commonly used X-ray detector, and is suitable for replacing the scintillator of commercial X-ray flat-panel detection.
[0055] The present invention also provides an application of a thallium-doped copper-based halide powder or a thallium-doped scintillator film in the field of radiation detectors; wherein the thallium-doped copper-based halide powder is the above-mentioned thallium-doped copper-based halide powder or the thallium-doped copper-based halide powder prepared by the above-mentioned preparation method; the thallium-doped scintillator film is the above-mentioned thallium-doped scintillator film or the thallium-doped scintillator film prepared by the above-mentioned preparation method.
[0056] The following is a more specific example of a thallium-doped copper-based halide powder, a thallium-doped scintillator film, a method for preparing a thallium-doped copper-based halide powder, and a method for preparing a thallium-doped scintillator film. It should be noted that the example is only a specific example of the present invention and cannot limit the scope of protection of the present invention.
[0057] Embodiment 1:
[0058] S1, placing 2 g of solid materials of CsI, CuI and TlI with a molar ratio of 3:2:0.02, 2 mL of anhydrous ethanol and agate balls in a ball mill with a volume of 50 mL, the mass ratio of agate balls to solid materials being 20:1, and evacuating the ball mill and placing it in a ball mill to prepare thallium-doped copper-based halide powder by wet grinding, the ball mill speed being 1000 r / min, and the ball milling time being 5 h;
[0059] S2, collecting the thallium-doped copper-based halide powder obtained in step S1 into a centrifuge tube, centrifuging at 5000 r / min for 5 min, discarding the supernatant, taking the precipitate, and centrifuging at 120 o C drying for 5 h, collecting the thallium-doped copper-based halide powder;
[0060] S3, mixing the thallium-doped copper-based halide powder obtained in S2 with PVB at a mass ratio of 25:1, adding toluene, and stirring thoroughly to obtain a powder dispersion with a concentration of 300 mg / mL;
[0061] S4, prepare the thallium-doped scintillator film by drop coating. 2 3 mL of the powder dispersion obtained in S3 was dripped onto the substrate, and the film was placed in a glove box to stand, and the initial thallium-doped scintillator film was obtained after the solvent evaporated slowly;
[0062] S5, placing the initial thallium-doped scintillator film obtained in S4 into a hot press at a pressure of 10t and a temperature of 200 o C, the hot pressing time is 1 min, and a thallium-doped scintillator film is obtained.
[0063] Comparative Example 1:
[0064] The difference between this comparative example 1 and Example 1 is that Example 1 uses solid materials of CsI, CuI and TlI with a molar ratio of 3:2:0.02 to prepare thallium-doped copper-based halide powder, while Comparative Example 1 uses solid materials of CsI and CuI with a molar ratio of 3:2 to prepare copper-based halide powder. The specific method is as follows:
[0065] S1, placing 2 g of CsI and CuI solid materials with a molar ratio of 3:2, 2 mL of anhydrous ethanol and agate balls in a 50 mL ball mill, the mass ratio of agate balls to solid materials being 20:1, and evacuating the ball mill and placing it in a ball mill to prepare copper-based halide powder by wet grinding, the ball mill speed being 1000 r / min, and the ball milling time being 5 h;
[0066] S2, collect the powder obtained in step S1 into a centrifuge tube, centrifuge at 5000r / min for 5min, pour off the supernatant, take the precipitate, and centrifuge at 120 oC drying for 5 h, collecting the copper-based halide powder;
[0067] S3, mixing the copper-based halide powder obtained in S2 with PVB at a mass ratio of 25:1, adding toluene, and stirring thoroughly to obtain a powder dispersion with a concentration of 300 mg / mL;
[0068] S4, scintillator film was prepared by drop coating. 2 3 mL of the powder dispersion obtained in S3 was added dropwise onto the substrate, and the film was placed in a glove box to stand, and the initial scintillator film was obtained after the solvent evaporated slowly;
[0069] S5, the initial scintillator film obtained in S4 is placed in a hot press and hot pressed at a pressure of 10t and a temperature of 200 o C, the hot pressing time is 1 min, and the scintillator film is obtained.
[0070] Figure 1 The photoluminescence spectra of the scintillator film obtained in Comparative Example 1 of the present invention and the thallium-doped scintillator film obtained in Example 1 under irradiation with 310 nm ultraviolet light are shown.
[0071] Depend on Figure 1 It can be seen that the thallium-doped scintillator film obtained by the preparation method provided by the present invention has enhanced photoluminescence intensity under 310nm ultraviolet light irradiation, and the luminescence wavelength is red-shifted from around 450nm to around 510nm, compared with the scintillator film not doped with thallium.
[0072] Figure 2 The figure shows the surface morphology of the thallium-doped scintillator film obtained in Example 1 of the present invention observed by a scanning electron microscope; Figure 3 The cross-sectional morphology of the thallium-doped scintillator film obtained in Example 1 of the present invention observed by a scanning electron microscope is shown; Figure 4 The cross-sectional layered diagram of the thallium-doped scintillator film obtained in Example 1 of the present invention observed by an energy dispersive X-ray spectrometer is shown; Figure 5 Shown with Figure 4 Correspondingly, the distribution diagram of each element in the cross section of the thallium-doped scintillator thin film obtained in Example 1 of the present invention.
[0073] The thallium-doped scintillator film obtained in Example 1 was subjected to morphological characterization and elemental analysis. Figure 2~Figure 4 As shown in FIG. 1 , it can be seen from the surface morphology of the thallium-doped scintillator film that the thallium-doped scintillator film prepared using the thallium-doped copper-based halide powder is uniformly distributed. Figure 5 The successful preparation of thallium-doped scintillator film can be seen in a~d.
[0074] Figure 6The radiant luminescence spectra of the CsI:Tl crystal and the thallium-doped scintillator film obtained in Example 1 of the present invention under X-ray irradiation are shown; Figure 7 The time-resolved photoluminescence spectrum of the thallium-doped scintillator film obtained in Example 1 of the present invention under irradiation of a 369nm laser pulse is shown.
[0075] Depend on Figure 6 It can be seen that the thallium-doped scintillator film obtained by the preparation method provided by the present invention has enhanced radiation luminescence intensity and similar luminescence wavelength under X-ray irradiation compared with CsI:Tl crystal. Under 310nm ultraviolet light irradiation, the photoluminescence intensity of the thallium-doped scintillator film is enhanced, and the luminescence wavelength is red-shifted from around 450nm to around 510nm.
[0076] Depend on Figure 7 It can be seen that the fluorescence decay lifetime of the thallium-doped scintillator film obtained by the preparation method provided by the present invention is short, about 437 ns.
[0077] According to an embodiment of the present invention, the thallium-doped copper-based halide powder provided by the present invention has a + As a substitution doping of alkali metal in copper-based halide, the conduction band minimum value of the copper-based halide energy level structure is reduced, thereby reducing its band gap, red-shifting the emission wavelength, and the halogen element. Therefore, compared with copper-based halide powder not doped with thallium, the emission wavelength of thallium-doped copper-based halide powder is red-shifted to around 510nm, and the fluorescence quantum efficiency is high (about 92%), and the fluorescence decay lifetime is short (about 437ns). Since the emission wavelength of thallium-doped copper-based halide powder is relatively matched with the emission wavelength (around 550nm) of the scintillator (such as CsI:Tl, GOS:Tb) of commercial X-ray flat panel detectors, the thallium-doped copper-based halide powder provided by the present invention can be used to prepare a scintillator film to replace the scintillator layer in the commercial X-ray flat panel detector, while ensuring good fluorescence performance.
[0078] The above specific embodiments further illustrate the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a thallium-doped scintillator film, It is characterized in that The preparation method comprises: Using a wet grinding method, solid materials of AX, CuX and TlX and a solvent insoluble in the solid materials are ground to obtain thallium-doped copper-based halide powder; The thallium-doped copper-based halide powder, the polymer composite material and the dispersant are mixed to obtain a powder dispersion, wherein the chemical composition formula of the thallium-doped copper-based halide powder includes: A 3 Cu 2 X 5 :TlX, A represents an alkali metal element, and X represents a halogen element; Forming a film on the powder dispersion to obtain the thallium-doped scintillator film; Wherein, the polymer composite material comprises one of the following: polymethyl methacrylate, polydimethylsiloxane, polyvinyl butyral; Wherein, when the polymer composite material is determined to be the polymethyl methacrylate, the mass ratio of the thallium-doped copper-based halide powder to the polymer composite material is 1:1-2:1; when the polymer composite material is determined to be the polydimethylsiloxane, the mass ratio of the thallium-doped copper-based halide powder to the polymer composite material is 1:1-10:1; when the polymer composite material is determined to be the polyvinyl butyral, the mass ratio of the thallium-doped copper-based halide powder to the polymer composite material is 25:1-500:1; Wherein, the film-making method includes: drop coating method; The step of forming a film from the powder dispersion to obtain the thallium-doped scintillator film comprises: applying the powder dispersion droplets on a substrate so as to obtain an initial thallium-doped scintillator film after the dispersant is volatilized; After hot pressing the initial thallium-doped scintillator film, the thallium-doped scintillator film is obtained; The hot pressing pressure is 5-20t; The temperature of the hot pressing is 100~300 o C; The heat pressing time is 1 to 10 minutes; Wherein, the molar ratio of the AX to the CuX is 3:2; The molar ratio of the TlX to the AX is 0.02:
3.
2. The preparation method according to claim 1, It is characterized in that The dispersant includes at least one of the following: dimethylformamide, dimethyl sulfoxide, γ-hydroxybutyrolactone, β-mercaptoethanol, nitrogen methyl pyrrolidone, dimethylacetamide, anhydrous ethanol and toluene.
3. The preparation method according to claim 1, It is characterized in that The alkali metal element includes at least one of the following: Cs + 、Na + , K + , Rb + ; The halogen element includes at least one of the following: I - Br - , Cl - .
4. The preparation method according to claim 1, It is characterized in that The grinding time is 3 to 12 hours; The grinding speed is 500-2000 r / min.
Citation Information
Patent Citations
Preparation method of non-lead copper-based halide scintillator film
CN112442360A
Thallium-doped Cs3Cu2I5 nanocrystalline scintillator with high light yield
CN113136203A
High-resolution flexible copper-based halide film for X-ray imaging and preparation process thereof
CN116285947A
Flexible lead-free high-energy radiation protective film as well as preparation method and application thereof
CN117624895A
